Negotiation and power in dialogic interaction - Weigand, Edda; Dascal, Marcelo (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2001)
The topic of negotiation has turned out to be of crucial interdisciplinary interest for our understanding of what we are doing in language use. Are we exchanging meanings defined in advance and presupposing equal understanding on the basis of a rule-governed system, or are we negotiating meaning and understanding in the framework of an open dialogic universe? Negotiation, on the one hand, can be taken as the name of a specific dialogue type or action game of bargaining. On the other hand, it represents a methodological concept for describing and explaining dialogic interaction which replaces t.